Alternative Techniques to Large Urban Networks: The Misunderstandings about the Success of On-Site Composting in Paris. Issue 3 (2nd July 2020) - Lehec, Elisabeth
ABSTRACT: In countries of the North, shared on-site composting has been popular with actors, institutions, and inhabitants. Based on field work conducted in Paris, this article shows that public institutions are disqualifying these low-tech techniques for providing urban services, while residents involved in composting do it mostly for pleasure. This difference in the aims of decentralized techniques and large networks merits being taken into account when designing more efficient urban services, which can connect large networks and on-site techniques. Achieving such coordination would imply reversing the way in which urban services are organized. Instead of setting up techniques that uniformly collect waste throughout a territory, services should be designed in view of the demand for the finished product. This leads to questioning the concept of public service and asking what a city has to offer to its inhabitants. Does a city owe its inhabitants a uniform collection system, while reducing the waste that goes into landfills? Or should it guarantee a long-term reduction in the generation of the amount of waste produced?